The expansion and establishment of the New Zealand mud snail Potamopyrgus antipodarum (Gray, 1843) in the freshwater ecosystems of Madeira Island (NE Atlantic) - Órfão, Inês (2024)
This study reports the spread of the New Zealand mud snail Potamopyrgus antipodarum throughout freshwater ecosystems of Madeira Island, located in the NE Atlantic. Potamopyrgus antipodarum was first detected in 2017–2018 in two streams located in the north coast of the island. Since then, we have visually inspected the island's freshwater ecosystems and detected this gastropod in nine other streams. Previous evidence suggests that this species was introduced to Madeira since at least 2017, likely in the northern part. Our findings indicate that P. antipodarum is now well established in the initial invaded locations and has since spread to the south region and upper streams of the island. Although it is difficult to conclusively determine the origin and vector of this introduction, it is plausible to assume that humans and fish may have contributed to its current distribution. Our records represent the first evidence of vast geographical distribution of P. antipodarum on Madeira Island. Madeira seems to be the first invaded oceanic island of Macaronesia and the westernmost European distribution range for this invasive species.